Specific questionnaire detects a high incidence of intra-operative hypersensitivity reactions - Laila S. Garro; Marcelo V. Aun; Iracy Sílvia C. Soares; Marisa R. Ribeiro; Antônio A. Motta; Jorge Kalil; Mariana C. Castells; Maria José C. Carmona; Pedro Giavina-Bianchi (Clinics, 2018)
OBJECTIVE: To assess the incidence of intra-operative immediate hypersensitivity reactions and anaphylaxis. METHODS: A cross-sectional observational study was conducted at the Department of Anesthesiology, University of São Paulo School of Medicine, Hospital das Clínicas, São Paulo, Brazil, from January to December 2010. We developed a specific questionnaire to be completed by anesthesiologists. This tool included questions about hypersensitivity reactions during anesthesia and provided treatments. We included patients with clinical signs compatible with immediate hypersensitivity reactions. Hhypersensitivity reactions were categorized according to severity (grades I-V). American Society of Anesthesiologists physical status classification (ASA 1-6) was analyzed and associated with the severity of hypersensitivity reactions. RESULTS: In 2010, 21,464 surgeries were performed under general anesthesia. Anesthesiologists answered questionnaires on 5,414 procedures (25.2%). Sixty cases of intra-operative hypersensitivity reactions were reported. The majority patients (45, 75%) had hypersensitivity reactions grade I reactions (incidence of 27.9:10,000). Fifteen patients (25%) had grade II, III or IV reactions (intra-operative anaphylaxis) (incidence of 7:10,000). No patients had grade V reactions. Thirty patients (50%) were classified as ASA 1. The frequency of cardiovascular shock was higher in patients classified as ASA 3 than in patients classified as ASA 1 or ASA 2. Epinephrine was administered in 20% of patients with grade III hypersensitivity reactions and in 50% of patients with grade II hypersensitivity reactions. CONCLUSIONS: The majority of patients had hypersensitivity reactions grade I reactions; however, the incidence of intra-operative anaphylaxis was higher than that previously reported in the literature. Patients with ASA 3 had more severe anaphylaxis; however, the use of epinephrine was not prescribed in all of these cases. Allergists and anesthesiologists should implement preventive measures to reduce the occurrence of anaphylaxis.